Immunohistochemical analysis of huntingtin-associated protein 1 in adult rat spinal cord and its regional relationship with androgen receptor. (6th January 2017) - Islam, Md. Nabiul; Takeshita, Yukio; Yanai, Akie; Imagawa, Amami; Jahan, Mir Rubayet; Wroblewski, Greggory; Nemoto, Joe; Fujinaga, Ryutaro; Shinoda, Koh
Graphical abstract: Highlights: HAP1 is abundantly expressed in spinal neurons of the somatosensory, viscerosensory and autonomic regions. More than 80% of neurons expressed both HAP1 and androgen receptor (AR) in the dorsal horn and around the central canal. HAP1 was completely lacking in the spinal motoneurons with or without AR expression. Due to lack of putative HAP1 protectivity, motoneurons might be more vulnerable to stresses in neurodegenerative diseases. Abstract: Huntingtin-associated protein 1 (HAP1) is a neuronal interactor with causatively polyglutamine (polyQ)-expanded huntingtin in Huntington's disease and also associated with pathologically polyQ-expanded androgen receptor (AR) in spinobulbar muscular atrophy (SBMA), being considered as a protective factor against neurodegenerative apoptosis. In normal brains, it is abundantly expressed particularly in the limbic-hypothalamic regions that tend to be spared from neurodegeneration, whereas the areas with little HAP1 expression, including the striatum, thalamus, cerebral neocortex and cerebellum, are targets in several neurodegenerative diseases. While the spinal cord is another major neurodegenerative target, HAP1-immunoreactive (ir) structures have yet to be determined there. In the current study, HAP1 expression was immunohistochemically evaluated in light and electron microscopy through the cervical, thoracic, lumbar, and sacral spinal cords of the adult male rat. Our results showed that HAP1 is specifically expressed in neurons through the spinal segments and that more than 90% of neurons expressed HAP1 in lamina I–II, lamina X, and autonomic preganglionic regions. Double-immunostaining for HAP1 and AR demonstrated that more than 80% of neurons expressed both in laminae I-II and X. In contrast, HAP1 was specifically lacking in the lamina IX motoneurons with or without AR expression. The present study first demonstrated that HAP1 is abundantly expressed in spinal neurons of the somatosensory, viscerosensory, and autonomic regions but absent in somatomotor neurons, suggesting that the spinal motoneurons are, due to lack of putative HAP1 protectivity, more vulnerable to stresses in neurodegenerative diseases than other HAP1-expressing neurons probably involved in spinal sensory and autonomic functions.